Everyday Experiences of Statelessness in the UK - ELEANOR COTTERILL (2022)
This thesis explores the everyday experiences of stateless people residing in the UK. Through a slow, creative, participatory methodology, this study grounds and expands understandings of everyday statelessness using scrapbooking techniques. By conceptualising statelessness as a lived experience, this thesis expands understandings of the status beyond an abstract legal conundrum or category of non-citizenship. This conceptualisation does not discount statelessness as a legal phenomenon, but acknowledges statelessness as a complex political, social, and cultural status rooted in lived experience. A focus on everyday topics (services, home and leisure), exposes how statelessness becomes present taking multiple forms, emerging through and impacting mundane spaces and encounters. Revealing the ambiguities and contradictions in and through the everyday lives of stateless persons. However, the multiple banal forms of statelessness can make the condition seem intangible and elusive. Creative approaches to research are a means to bring to the fore the overlooked and challenge the settled. Through creative, ethnographic research with stateless individuals in Cardiff and London, this thesis explores how creative, participatory research methodologies can be ethically utilised with vulnerable populations. Using feminist methodological approaches, this study develops and employs scrapbooking as a form of elicitation with stateless persons. The approach is critically examined: asking what alternative insights into statelessness does a slow, participatory, creative approach elicit? It demonstrates how the highly visual practice of scrapbooking assists stateless participants to reveal previously hidden everyday experiences, emphasising in layouts their principal concerns and raising awareness of their everyday lives in the UK. Through revealing everyday experiences of statelessness in the UK, this thesis challenges the narrative that the status is exceptional, demonstrating that statelessness is ever-present and ongoing throughout the everyday in the UK.